Evaluating Contribution of Flipped Learning on Secondary Students’ Critical Thinking Skills Toward Learning Physics in Palestine - Atwa, Zaher; Din, Rosseni; Othman, Nabilah; Hussin, Muhammad (International Journal of Engineering and Technology, 2018)
The aim of this study is to examine the effects of Flipped Learning on Palestinian secondary school students’ critical thinking skills. Flipped Learning is a new approach in ICT to improve teaching and learning process and create learning opportunity in a very limited time for high school students in a country at war like Palestine. Physics is too difficult for most students and this leads to poor academic performance and achievements. There is a need to improve learning physics with critical thinking skills for secondary school students in order to enable their advancement for higher education. The application of flipped learning is interesting, interactive and attractive for students. There is no research on Palestinian secondary schools concerning the effects of flipped learning on critical learning skills. In order to comply with the set objectives, the researcher developed video lessons by utilizing technology in Physics topics for students to view the lessons through Facebook groups outside school hours. Quasi-experimental method was used. 108 grade 11 students were selected purposively. California Critical Thinking Skills Test was adopted and administered for the students after pretest and posttest. Descriptive and inferential statistics was used to analyze the data with T-tests and ANCOVA test. The pretest and posttest scores were not statistically significant for both groups. It is found that the added value between the pretest and posttest for the flipped learning students is 20.0% which is higher than that of the conventional students at 6.5%. This approach suggests that there were positive effects of the students' critical thinking skills when using flipped learning method.